Haematopoietic cell transplantation in Switzerland, changes and results over 20 years: a report from the Swiss Blood Stem Cell Transplantation Working Group for Blood and Marrow Transplantation registry 1997–2016 (Swiss Medical Weekly, 2018)
In 1997, the Swiss Blood Stem Cell Transplantation Group (SBST) initiated a mandatory national registry for all haematopoietic stem cell transplants (HCTs) in Switzerland. As of 2016, after 20 years, information was available for 7899 patients who had received an HCT (2781 allogeneic [35%] and 5118 autologous [65%]). As some patients had more than one transplant the total number of transplants was 3067 allogeneic and 6448 autologous. We compared patient characteristics and outcome of the first decade (1997–2006) and second decade (2007-2016) of the registry. There were numerous changes over time. For allogeneic HCT, transplant rates, and therefore use of HCT technology, increased from 14 to 21.8 HCTs per 1 million inhabitants per year from the first to the second decade. Likewise autologous HCTs increased from 24.8 to 37.2 annually corrected for population growth. Allogeneic transplant recipients were older (38.4 vs 48.3 years) and more frequently had unrelated donors in the second decade. Similarly, age increased for recipients of autologous HCT (50.8 vs 56.4 years). Analysis of outcome showed that the probabilities of overall and progression-free survival were stable over time, in spite of the treatment of older and higher risk patients. In multivariate analysis, nonrelapse mortality decreased in recipients of allogeneic HCT (relative risk 0.68, 95% confidence interval 0.52–0.87) over the two decades. Improvement in adjusted nonrelapse mortality compensated for the fact that higher risk patients were treated in more recent years, resulting in similar overall survival. Five-year survival probabilities were 56% (53–59%) in the first and 54% (51–57%) in the second decade for allogeneic HCT, and 59% (57–61%) in the first and 61% (59–63%) in the second decade for autologous HCT. Detailed analyses of changes over time are presented. This study included all HCTs performed in Switzerland during the period of observation and the data are useful for quality assurance programmes, healthcare cost estimation and healthcare planning. Between 50 and 60% of patients were long-term survivors after both types of HCT, indicating growing populations of surviving patients requiring long-term care and observation.